Inflammasomes in neuroinflammation and changes in brain function: a focused review - Singhal, Gaurav; Jaehne, Emily J.; Corrigan, Frances; Toben, Catherine; Baune, Bernhard T. (Frontiers in Neuroscience, 2014)
Recent literature has pointed to the existence of inflammasome-mediated inflammatory pathways in central nervous system disorders and associated changes in behavior. Neuroinflammation, which is an innate immune response in the central nervous system against harmful and irritable stimuli such as pathogens and metabolic toxic waste, as well as to chronic mild stress, is mediated by protein complexes known as inflammasomes. Inflammasomes activate pro-inflammatory caspases 1 and 5, which then cleave the precursor forms of pro-inflammatory cytokines IL-1β, IL-18 and IL-33 into their active forms. These pro-inflammatory cytokines have been shown to promote a variety of innate immune processes associated with infection, inflammation and autoimmunity, and thereby play an instrumental role in the instigation of neuroinflammation during old age and subsequent occurrence of neurodegenerative diseases, cognitive impairment and dementia. In particular, NLRP inflammasomes may also have a role in the etiologies of depression, Alzheimer’s disease and in metabolic disorders, such as Type II diabetes, obesity and cardiovascular diseases that have been shown to be co-morbid with psychiatric illnesses. It has been reported that while these inflammasomes may be activated through TNF-α dependent pathways, other cytokines, like IFN-γ, may assist in inhibiting their activation and thus delay disease progression. Furthermore some other cytokines, including IL-6, may not have a direct role in inflammasome-mediated diseases. An array of recent research suggests that NLRP inflammasomes targeted therapies could be used for alleviating neuroinflammation and for treatment of associated psychiatric illnesses, although this still remains a challenge and necessitates further extensive research. This review examines the complex inflammatory signaling pathways involved in the activation of NLRP inflammasomes and the role they play in promoting neuroinflammation and subsequent behavioral changes.